(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A list is given of the Aphids found, during the course of a number of years (1980-1994), on the principal trees that make up the woodland of the upper Val Camonica, in central Alps. It comprises 46 species belonging to various families and subfamilies, the main ones being Lachninae (47%) and Phyllaphidinae (31% ). Biological data of each species are recorded, and the ant species with which they are associated. This study has permitted the drawing up of a geonemic chart of the aphid population of the territory under consideration, comparable with the already noted of the eastern sector of the Alps.